2014
DOI: 10.1111/1471-0528.12696
|View full text |Cite
|
Sign up to set email alerts
|

Chewing gum in preventing postoperative ileus in women undergoing caesarean section: a systematic review and meta‐analysis of randomised controlled trials

Abstract: Background The incidence of postoperative ileus (POI) after gynaecological surgery is 10-15% Chewing gum following general surgery improves outcomes, including early flatus, early bowel sounds, and shortening of hospitalisation periods. There is currently no guideline that supports the use of chewing gum after caesarean sections.Objectives To systematically analyse the published randomised controlled trials regarding the effectiveness of chewing gum in preventing POI in women undergoing caesarean sections.Sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 35 publications
3
30
0
1
Order By: Relevance
“…A recent meta-analysis by Huang [12] included only five RCTs involving 882 patients, the sample size and number of included studies were small. An earlier meta-analysis by Hochner [15] also included five RCTs with a total of 846 participants, the process for meta-analysis was rather strict, yet the publication bias could not be evaluated quantitatively by a funnel plot due to the small number of studies available, the other meta-analyses [14, 16, 17] also had problems in this area. Another comprehensive Cochrane meta-analysis [13] identified 81 studies involving 9072 participants to investigate whether the chewing gum after surgery hasten the return of gastrointestinal function after abdominal surgery, come to the finding that gum chewing showed a beneficial impact on the major outcomes of digestive system activation, including bowel sound, flatus passage and bowel movement, yet the including studies were rather heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis by Huang [12] included only five RCTs involving 882 patients, the sample size and number of included studies were small. An earlier meta-analysis by Hochner [15] also included five RCTs with a total of 846 participants, the process for meta-analysis was rather strict, yet the publication bias could not be evaluated quantitatively by a funnel plot due to the small number of studies available, the other meta-analyses [14, 16, 17] also had problems in this area. Another comprehensive Cochrane meta-analysis [13] identified 81 studies involving 9072 participants to investigate whether the chewing gum after surgery hasten the return of gastrointestinal function after abdominal surgery, come to the finding that gum chewing showed a beneficial impact on the major outcomes of digestive system activation, including bowel sound, flatus passage and bowel movement, yet the including studies were rather heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…The use of chewing gum in women undergoing caesarean sections also reduces the risk of POI, but does not affect the length of hospitalisation. 9 Nimrata et al concluded that use of chewing gum in the postoperative period is a safe and cheap method to stimulate bowel motility and reduce the postoperative ileus after abdominal surgery. 17 …”
Section: Discussionmentioning
confidence: 99%
“…It may be a normal, physiological response to abdominal surgery, but may also occur in patients after other forms of surgery. The pathogenesis of postoperative ileus is not fully understood and causation is likely to be multifactorial . The incidence of ileus after gynaecological procedures has been estimated to be 10–15% although there is a paucity of specific data for caesarean section.…”
Section: Postoperative Ileusmentioning
confidence: 99%
“…The pathogenesis of postoperative ileus is not fully understood and causation is likely to be multifactorial. 33 The incidence of ileus after gynaecological procedures has been estimated to be 10-15% although there is a paucity of specific data for caesarean section. A 2014 systematic review examining the role of chewing gum in reducing postoperative ileus after caesarean section suggested an incidence of approximately 12% in the control group and that chewing gum may reduce the risk to 5%.…”
Section: Postoperative Ileusmentioning
confidence: 99%